2020
DOI: 10.1074/jbc.ra120.013100
|View full text |Cite|
|
Sign up to set email alerts
|

The barley lectin, horcolin, binds high-mannose glycans in a multivalent fashion, enabling high-affinity, specific inhibition of cellular HIV infection

Abstract: N-linked glycans are critical to the infection cycle of HIV, and most neutralizing antibodies target the high-mannose glycans found on the surface envelope glycoprotein-120 (gp-120). Carbohydrate-binding proteins, particularly mannose-binding lectins have also been shown to bind these glycans. Despite their therapeutic potency their ability to cause lymphocyte proliferation limits their application.   In this study we report one such lectin named Horcolin (Hordeum vulgare lec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 56 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…Similarly, the chitin elicitor receptor kinase 1 (CERK1), initially reported to directly bind chitin oligosaccharides, has been suggested to function as a co-receptor for linear (1,3)- β -D-glucan, triggering fungal immune responses in A. thaliana , recently [ 58 ]. Recently, the multivalent binding of horcolin to high-mannose glycans has been demonstrated [ 59 ]. Whether a similar function may be assigned to HvHorcH remains speculation at this point.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the chitin elicitor receptor kinase 1 (CERK1), initially reported to directly bind chitin oligosaccharides, has been suggested to function as a co-receptor for linear (1,3)- β -D-glucan, triggering fungal immune responses in A. thaliana , recently [ 58 ]. Recently, the multivalent binding of horcolin to high-mannose glycans has been demonstrated [ 59 ]. Whether a similar function may be assigned to HvHorcH remains speculation at this point.…”
Section: Discussionmentioning
confidence: 99%
“…The binding of mannose-specific banana lectin with HIV surface protein was studied in detail and found as a promising anti-HIV lectin [ 19 ]. Horcolin, a lectin from Hordeum vulgare, showed sugar-binding specificity towards high mannose sugars (Man5/7/9) and confirmed that it can bind with recombinant gp120 and gp140 with high affinity and inhibition of HIV infection at 30–35 nM concentrations without mitogenicity [ 23 ] (Table 1 ).
Fig.
…”
Section: Plant Lectins With Antiviral Propertiesmentioning
confidence: 96%
“…Although most plant lectins with antiviral activity activate different sets of T lymphocytes and, more scarcely, B lymphocytes, they also activate both the apoptotic and necrotic pathways in many other types of healthy and cancer cells [134][135][136][137][138][139][140][141][142][143]. The cellular activation mediated by plant lectins on healthy and transformed cells elicits the release of various chemokines and/or cytokines that are, in turn, susceptible to interfere with the cytokine stimulation associated with the viral infection, e.g., HIV infection [59]. However, plant lectins readily differ from each other by their capacity to elicit a cytokine production, some of them, such as PHA, Con A, and cyanovirin-N, being more active to induce the synthesis and release of activation markers [144,145], while Man-specific GNA-like lectins, such as GNA and HHA, were virtually incapable of triggering a relevant cytokine production [145,146].…”
Section: Biomedical Perspectives For Antiviral Lectinsmentioning
confidence: 99%